Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/jp107447q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aqueous and Nonaqueous Iron Oxide Nanofluids and Study of Temperature Dependence on Thermal Conductivity and Viscosity

Abstract: We investigate the temperature-dependent thermal conductivity (k) of aqueous and nonaqueous stable nanofluids with average particles size of 8 nm stabilized with a monolayer of surfactant. Iron oxide (Fe3O4) nanoparticles are synthesized by a coprecipitation technique and are characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), vibrating sample magnetometry (VSM), dynamic light scattering (DLS), and theromogravimetric analysis (TGA). The particles are functionalized with sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(90 citation statements)
references
References 112 publications
(436 reference statements)
7
81
0
1
Order By: Relevance
“…Previous works involving enhanced thermal conductivity of water usually comprises addition of CuO, [20][21][22] Al 2 O 3 6,22-24 and iron oxide 25,26 to water and all agreed on enhancement in thermal conductivity upon addition of NPs.…”
Section: Deterioration In Relative Thermal Conductivity Of Ag/w-dw Namentioning
confidence: 99%
“…Previous works involving enhanced thermal conductivity of water usually comprises addition of CuO, [20][21][22] Al 2 O 3 6,22-24 and iron oxide 25,26 to water and all agreed on enhancement in thermal conductivity upon addition of NPs.…”
Section: Deterioration In Relative Thermal Conductivity Of Ag/w-dw Namentioning
confidence: 99%
“…13 It was also shown that at the same volume fractions, Fe 3 O 4 nanofluids have higher thermal conductivity than other metal oxide nanofluids such as CuO, TiO 2 , and Al 2 O 3 as a result of nanoparticle alignment. 26 Although the thermal conductivity of aqueous nanofluids increases, while that of non-aqueous nanofluids decreases with temperature, the ratio of the nanofluid thermal conductivity to base fluid thermal conductivity remains constant, 25,27 implying that the temperature dependency of thermal conductivity does not change upon addition of nanoparticles. This enhancement in thermal conductivity was found to be higher 19,26 than predictions by the effective medium theory (EMT) proposed by Maxwell 28 and other theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Shima et al reported an enhancement in thermal conductivity of water-based magnetic nanofluids having the same tetramethyl ammonium hydroxide layer stabilizing the particles. 27 On the other hand, Wang et al 34 showed an enhancement in thermal conductivity for oleic acid coated magnetite particles dispersed in toluene. The same particles dispersed in water after ligand exchange with poly(acrylic acid) showed a fluctuating trend for the thermal conductivity change as a function of particle concentration, which was attributed to the aggregation of particles leading to an increase in interfacial thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer-sized stable metal, metal oxides or carbon particles in various forms could be suspended in the industrial heat transfer fluids (water and organic liquids), and can result in anomalously large enhancements of the thermal conductivities. [1][2][3][4][5] These reports show that only 5 vol. % of nanoparticles such as alumina (Al 2 O 3 ), copper oxide (CuO), and copper (Cu) dispersed in different base fluids, the thermal conductivity of the nanofluids was observed a significant improvement ($60%) as compared to the corresponding base fluids.…”
Section: Introductionmentioning
confidence: 98%